Funkcjonowanie partnerstw międzysektorowych w opinii ich członków. Przykład lokalnych grup działania województwa podkarpackiego - Pawłowska, Agnieszka; Gąsior-Niemiec, Anna; Kołomycew, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
The notion of intersectoral partnership is understood in the paper in terms of voluntary and institutionalized cooperation between stakeholders representing public, private and civic sectors. The idea of this kind of partnership is related to new approaches to regional and local development in the European Union. One of the main fields in which these approaches are implemented is the field of rural areas development, where partnerships take the form of Local Action Groups (LAGs). The paper discusses selected aspects of the partnerships’ functioning, basing on an analysis of opinions expressed by their individual members in the Sub-Carpathian region.
THE FUNCTIONING OF MULTISECTOR PARTNERSHIPS IN THE OPINION OF THEIR MEMBERS. CASE STUDY OF THE LOCAL ACTION GROUPS IN THE SUB-CARPATHIAN REGION
Keywords: inter-sector partnerships; rural areas; Local Action Group; Sub-Carpathian region